Two cases of esophageal basaloid squamous cell carcinoma which achieved long‐term survival by endoscopic submucosal dissection and additional chemoradiotherapy. Issue 1 (31st January 2023) - Morihisa, Yoshiki; Iwagami, Hiroyoshi; Akamatsu, Takuji; Nakano, Shogo; Wakita, Midori; Edagawa, Takeya; Konishi, Takafumi; Nakatani, Yasuki; Yamashita, Yukitaka
Abstract: Herein, we report two rare basaloid squamous cell carcinoma (BSCC) cases. Esophagogastroduodenoscopy revealed a submucosal tumor‐like lesion and a biopsied specimen showed a finding suspected of BSCC in both cases. Both lesions underwent endoscopic submucosal dissection with en bloc resection, and long‐term survival was achieved using additional chemoradiotherapy. The standard treatment for BSCC has not been determined, and there are few reports of esophageal BSCC treated using endoscopic resection. Endoscopic submucosal dissection and additional chemoradiotherapy for superficial BSCC may be effective treatment options.